AN IMPLEMENTATION OF TWO-FACTOR AUTHENTICATION TECHNOLOGY USING TIME-BASED ONE TIME PASSWORD (TOTP) METHOD ON PRIVATE CLOUD STORAGE WEBSITE FOR GUIDANCE AND COUNSELING TEACHER - Jerry Olbinson (Journal of Information Technology and Its Utilization, 2022)
Guidance and counseling teacher, as an assistant profession, provides counseling services for all students. In providing counseling services, the first activity to be performed is the collection of students’ data. The data collected are confidential. Technological advances in private cloud storage media and two-factor authentication can help the guidance and counseling teacher in the fulfillment of students’ data storage and protection. Cloud storage is one of the solutions in dealing with data management so that it is centralized and facilitates access for system users. It is also balanced with the security technology on an application to guarantee the data security in the application. The security technology of two-factor authentication can be combined with a password and time-based one-time password. A time-based one-time password is often used on an application that uses two-factor authentication with the combination of a secret key and current timestamp. This study aims to create a private cloud storage website for guidance and counseling teacher with two-factor authentication using the time-based one-time password method. This website has been tested with black-box testing and user testing. From the results of the tests, a private cloud storage website with two-factor authentication using the time-based one-time password method was well accepted by the users because it helps the guidance and counseling teacher in sharing data safely, and the results of the average percentage in all questions were 85%.